2020
DOI: 10.3390/ijms21175996
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptors Amplify CNS Damage in Neurodegenerative Diseases

Abstract: ATP is a (co)transmitter and signaling molecule in the CNS. It acts at a multitude of ligand-gated cationic channels termed P2X to induce rapid depolarization of the cell membrane. Within this receptor-channel family, the P2X7 receptor (R) allows the transmembrane fluxes of Na+, Ca2+, and K+, but also allows the slow permeation of larger organic molecules. This is supposed to cause necrosis by excessive Ca2+ influx, as well as depletion of intracellular ions and metabolites. Cell death may also occur by apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 246 publications
(316 reference statements)
2
74
0
Order By: Relevance
“…↑ OPC proliferation ↓ OPC differentiation [165] ↑ myelination [165,180] GABA B R ↑ proliferation and ↑ migration [181] ? ↑ differentiation [182] ATP/ADP P2X 7 R ↓ proliferation and ↑ migration [183] OL damage and myelin loss during ischemia or neuroinflammation [184,185] EAE-induced OL death by Ca 2+ overloading [186] P2Y 1 R ↑ migration [187,188] ? ↓ proliferation [188] P2Y 12 R ?…”
Section: Neurotransmitters In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
See 1 more Smart Citation
“…↑ OPC proliferation ↓ OPC differentiation [165] ↑ myelination [165,180] GABA B R ↑ proliferation and ↑ migration [181] ? ↑ differentiation [182] ATP/ADP P2X 7 R ↓ proliferation and ↑ migration [183] OL damage and myelin loss during ischemia or neuroinflammation [184,185] EAE-induced OL death by Ca 2+ overloading [186] P2Y 1 R ↑ migration [187,188] ? ↓ proliferation [188] P2Y 12 R ?…”
Section: Neurotransmitters In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…P2X 7 R activation mediates a rise in intracellular Ca 2+ , through direct influx by the channel pore, and activates multiple intracellular pathways, including MAPK, PKC, and PI3K, all involved in the regulation of OPC proliferation, differentiation and myelination. In addition, P2X 7 R also participates to OL damage and myelin loss during ischemia or neuroinflammation [ 184 , 185 ]. The facilitating role of P2X 7 R in OPC migration has been outlined by Feng et al who demonstrated that high concentrations of ATP or the P2X 7 R agonist BzATP increased the number of migrating OPCs in vitro, an effect abolished by pre-treatment with the P2X 7 R antagonist oxidized ATP [ 183 ].…”
Section: Neurotransmitters In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…It has also been proposed that an increase of calcium concentration from intracellular sources further activates Panx1 channels mediating an ATP-dependent ATP release, which further propagates calcium signaling to neighboring cells [ 22 ]. Moreover, Panx1 channels have been shown to form a complex with P2X7 purinergic receptors [ 88 ]; the latter are known to be molecular players that amplify CNS damage and neuroinflammation in various brain pathologies [ 89 ]. Various other plasma receptors or proteins involved brain pathologies, including NMDA receptors or caspases, have been linked to Panx1 channel activation ( Figure 2 ).…”
Section: Pannexin-1 (Panx1) Channelsmentioning
confidence: 99%
“…Overall, P2XR activities in glial cells are yet unclear, with the exception of P2X7, which engagement initiates the release of mediators whose nature differs between species [ 101 , 133 ].…”
Section: Expression Of P2xrs and The Role Of Atp And P2xr Activation In Neuroinflammationmentioning
confidence: 99%